Solvatochromic discrimination of alcoholic solvents by structural colors of polydopamine nanoparticle thin films - Lim, Yeon Su; Kim, Jong Sik; Choi, Jang Han; Kim, Ju Min; Shim, Tae Soup (Colloids and Interface Science Communications, 2022)
Structural color materials are promising sensory materials that exhibit a stable and stimuli responsive reflection color. To fully utilize their optical property as colorimetric sensors, a material having stimuli-sensitive and optically superior properties has to be applied for designing the structural color material. In this work, a solvatochromic structural color material made of multilayered polydopamine nanoparticles (PdNPs) is presented. Because PdNP has a high refractive index in the range of 1.7–2.0 and good swelling capability, it exhibits a notable solvatochromic behavior in various alcoholic solvents. The solvent sensing performance shows good reliability when compared with that of a refractive index sensing based structural color material. The dynamic reflection spectral patterns of the PdNP thin film upon solvent drying provides more information on the diffusion rate and surface tension of each target solvent. These results indicate that the PdNP thin film can be used to differentiate between physicochemically similar solvents.
Keywords: Colorimetric sensors; Polydopamine nanoparticles; Solvatochromic sensors; Structural colors; Thin film interferences